Application of multi-criteria-decision approach for the analysis of medical waste management systems in Myanmar. (10th June 2019) - Aung, Thiri Shwesin; Luan, Shengji; Xu, Qiyong
Abstract: Health-care services inevitably create medical waste that may become hazardous to public health and the environment. Nonetheless, a comprehensive and standardized evaluation framework to assess the status of medical waste management is currently lacking. This research developed a novel healthcare Waste Management evaluation framework based upon the World Health Organization (WHO) guidelines on the safe management of waste from health-care activities. The developed framework was then applied to 8 selected private and public hospitals in Myanmar to evaluate their medical waste management practices. Multi-Criteria Decision Making (MCDM) techniques were used to model the framework for the hospital waste management evaluation criteria. Structured questionnaires, observation checklists, and interviews were conducted to collect data from highly qualified healthcare personnel from Myanmar. The investigation evidenced that all the selected hospitals segregate medical wastes. However, disposal mostly involved open burning, incineration, and uncontrolled dumping. Deficiencies were also found in waste collection, storage, and transportation due to a serious lack of both onsite and offsite treatment facilities, especially for government hospitals. While basic awareness of healthcare staff about the risk and safe handling of medical waste was relatively high, the dissemination and enforcement of technical guidelines and regular monitoring of compliance were major concerns. This research highlights an urgent need for specific medical waste management laws and regulations, technologies, expert knowledge and funding to improve healthcare waste management in Myanmar. Highlights: AHP and ANP are used to assess medical waste management system in Myanmar. Segregation is the most important criteria for medical waste management in Myanmar. Collection, storage and transportation are influenced by proper segregation. Safety practices of the health workers are affected by knowledge and training. Areas of deficiency are treatment, collection, storage, transportation, training.